Complex Permittivity and Microwave‐Absorbing Properties of Fe/Al2O3 Coatings by Air Plasma Spraying Technique. (10th January 2013) - Zhao, Dong; Luo, Fa; Zhou, Wancheng; Zhu, Dongmei
Abstract : The Fe/Al2 O3 coatings for application as microwave absorbers were deposited by air plasma spraying (APS). The morphologies of powders and cross‐section of coatings were characterized by scanning electron microscope (SEM). The investigations of electrical conductivity and complex permittivity properties of coatings were performed. The real part (ε′) of permittivity increases with increasing Fe volume fraction, which is attributed to the space charge polarization, and the imaginary part (ε″) also increases which is ascribed to the increasing electrical conductivity result from the formation of Fe conductive network. The effect of Fe content on dielectric properties and the corresponding mechanisms are analyzed. By measuring the microwave absorption properties of the Fe/Al2 O3 coatings as a single‐layer absorbers, it was find that the reflection loss varies with the changes of thickness and Fe content, due to the deviation of impedance‐matching condition.